Class Representatives and Students’ Behaviour: An Overview at the Post-Covid-19 Pandemic in the Perspective of the Community of Practice - Dias, Ilane Frank; Bellucci, Christiane (International Journal of Educational Studies, 2021)
Engagement of students and the learning process in the classroom has become one of the significant challenges that higher education (HE) institutions face in the era of the Covid-19 pandemic, with classes running in the virtual environment. One of the approaches that can be used to understand student behaviours and their social interactions is the community of practice (CoPs) as a construct that can be strategic to connect classes representatives, college's objectives and the student's behaviour. The class representatives can play a diverse role, from helping the tutors motivate the students on their learning process to acting as a central and essential communication channel between the students and the academic coordinators. Yet, little is known about the role of these students as a strategy to tackle such problems increased with online classes. This study investigates the impact of class representatives on students' behaviour in the sense of their engagement and learning in virtual classes context post the Covid-19 pandemic. This is a conceptual paper to bridge the mentioned theories, link work across disciplines, provide multi-level insights, and broaden the scope of thinking. The theoretical findings show that class representatives can play a relevant role by increasing engagement and facilitating the students' learning. The results can help HE institutions to develop policies and practices to be more competitive and move forward. This study advances the emergent research efforts to respond to the challenges arising from the Covid-19 pandemic.